Globalization, institutions & governance - Caporaso, James A., 1941- (Sage series on the foundations of international relations, 2012)
"The study of international relations now goes well beyond state-to-state politics and even regional politics. Technological forces are working their effects on the world as a whole, bringing state and non-state actors into contact with one another. Globalization, Institutions and Governance provides students with a sophisticated and engaging exploration of the often differing impacts of these technological forces and the wider implications of globalization for theories of global governance and the role of international institutions"--Publisher's website.